Photo biomodulation of dental derived stem cells to ameliorate regenerative capacity: In vitro study - Alaa Medhat; Medhat A. El-Zainy; Iman Fathy (Elsevier, 2024)
Background: Dental regeneration benefits from improving the features of dental derived stem cells. Gallium-aluminum-arsenide laser had a significant role in modification of cell behavior in different cell lines and culture conditions. Hence, exploring its mechanism and effect on dental derived stem cells would benefit prospective regenerative dental therapies. Objectives: To assess the impact of photo biomodulation by Low-Level-Laser on isolated Dental Pulp derived Stem Cells and Periodontal Ligament derived Stem Cells regarding their proliferation and osteogenic differentiation. Methods: Isolated DPSCs and PDLSCs from impacted third molars were subjected to Gallium-aluminum-arsenide laser for 12 sec and 3.6 J/cm2. The proliferative capacity was evaluated via 3-(4,5-dimethylthiazol-2-yl),2,5-diphenyltetrazolium bromide (MTT) Assay and Trypan blue stain. Cell osteogenic differentiation potentials were assessed by alkaline phosphatase assay and alizarin red stain, polymerase chain reaction was performed to quantify Nuclear factor Kappa gene expression. Results: DPSCs subjected to laser bio-stimulation showed the best results regarding cell viability (MTT) and osteogenic differentiation (ALP assay), and calcium deposition at 3 intervals (3, 7, 14 days), meanwhile, PDLSCs subjected to laser bio-stimulation showed better result than control but less than DPSCs. While NF-KB gene expression was proven to be approximately comparable for both groups. Generally, the Photo-bio modulated groups showed better results than their control groups. Conclusion: Low-level laser bio-stimulation (LLL) therapy improves DPSC and PDLSC osteogenic differentiation and proliferation via the activation of the NF-KB pathway. Also, the DPSCs outperformed PDLSCs in terms of performance. Clinical significance: These results can be beneficial information and a reference database for more research in tissue engineering, dental therapy, and regeneration.